Ferritin levels in patients with COVID‐19: A poor predictor of mortality and hemophagocytic lymphohistiocytosis. (13th August 2020) - Feld, Jonathan; Tremblay, Douglas; Thibaud, Santiago; Kessler, Alaina; Naymagon, Leonard
Abstract: Introduction: A hyperinflammatory environment has been a hallmark of COVID‐19 infection and is thought to be a key mediator of morbidity. Elevated ferritin has been observed in many patients with COVID‐19. Several retrospective studies have shown ferritin levels can be correlated and predictive of poor outcomes in COVID‐19, though a rigorous analysis has been lacking. Methods: A retrospective analysis of 942 adult COVID‐19 patients admitted in March 2020 at a large New York City health system with available ferritin levels. Results: The primary outcome, all‐cause mortality, was observed in 265 (28.1%) patients. Patients who died had a significantly higher median admission and maximum ferritin levels than those who did not. However, death was poorly predicted by admission and maximum ferritin levels on receiver operator curve (ROC) analysis, with AUCs of 0.677 and 0.638, respectively. AUCs increased when the cohort was limited to progressively younger patients. Ferritin levels were minimally better at predicting our secondary outcomes. These included mechanical ventilation, observed in 280 (29.7%) patients with an ROC yielding an area under the curve (AUC) of 0.769, and new renal replacement therapy, observed in 80 (8.5%) of patients with an ROC yielding an AUC of 0.787. We also performed a subset analysis on 22 patients with ferritins >20 000 ng/mL. None of the patients met HLH‐2004 diagnostic criteria. Fifteen (68.2%) of these patients had suspected or confirmed bacterial infections. Conclusions: Though many patients with COVID‐19 present with hyperferritinemia, elevated ferritin levels are not accurate predictors of outcomes and do not appear to be indicative of hemophagocytic lymphohistiocytosis.